Business Development Service Through Lazis Partnership With Universities in Mentoring MSMEs in Purbalingga Regency - Nanda Jelis Septiana; Dani Kusumastuti (Profesional Muda Cendekia Publishing, 2022)
Indonesia is a country where most of yhe population is Muslim, where the potential for zakat funds is quite large so that it can be used as an alternative in minimizing existing poverty. With the obligtion of zakat, if can be used as a bridge to even out commonuty‟s economy, so that the gap between the rich and the poor will be reduced. We can pay zakat institutions, one of which is LAZIS Muhammadiyah, Purbalingga Regency. This institution itself was founded in 2002. During the course of the establishment of LAZIS Muhammadiyah, not only consumptive zakat funds were distributed to 8 groups of zakat recipients. However LAZISMU, Purbalingga also distributes and utiliez produvtive zakat for MSMEs who are joined with them form f Business Development Service through mentoring programs. Thus, this study aims to find out in more detail related to an assistance which will later be described in the formulation og the problem that the author has determined. The type of research in this research is field research. This research was conducted at LAZISMU, Purbalingga Regency with a descriptive-qualitative approach. Which descriptive it self describing and explaining the Business Development Service Through LAZIS Partenrship with Higher Education in Assisting MSMEs in Purbalingga Regency, this research was taken with data collection techniques in the form of observation, interviews, and documentation. The speakers are from the LAZIS, universitas, counterparts, and MSME actors. The results of research in the field related to Business Development Service through LAZIS Partenrship with Universities in Monitoring MSMEs in Purblingga Regency are as follows : (1)The effectiveness of the implementation of the Business Development Service. (2) Evaluation of the Business Development Service.